2010
DOI: 10.1158/1078-0432.ccr-10-0041
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Responses in a Phase II Study Using Adoptive Transfer of Short-term Cultured Tumor Infiltration Lymphocytes in Metastatic Melanoma Patients

Abstract: Purpose: Adoptive cell therapy with autologous tumor-infiltrating lymphocytes (TIL) has shown promising results in metastatic melanoma patients. Although objective response rates of over 50% have been reported, disadvantages of this approach are the labor-intensive TIL production and a very high drop-out rate of enrolled patients, limiting its widespread applicability.Previous studies showed a clear correlation between short TIL culture periods and clinical response. Therefore, we used a new TIL production tec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
374
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 409 publications
(391 citation statements)
references
References 21 publications
10
374
4
2
Order By: Relevance
“…4,5 , 35 Recent studies of adoptive transfer with autologous T cells generated from patients have focused on generation of genetically modified memory CD8 C T cells with chimeric antigen receptors or T-cell receptors with a particular focus on improving the proliferation and persistence of T cells after transfer. [36][37][38][39][40] Traditionally, IL-2 has been a central component of T-cell expansion protocols. [41][42][43] However, IL-2-expanded T cells have significant limitations in adoptive therapy, including susceptibility to T-cell activation-induced cell death (AICD), Treg proliferation, and T-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 , 35 Recent studies of adoptive transfer with autologous T cells generated from patients have focused on generation of genetically modified memory CD8 C T cells with chimeric antigen receptors or T-cell receptors with a particular focus on improving the proliferation and persistence of T cells after transfer. [36][37][38][39][40] Traditionally, IL-2 has been a central component of T-cell expansion protocols. [41][42][43] However, IL-2-expanded T cells have significant limitations in adoptive therapy, including susceptibility to T-cell activation-induced cell death (AICD), Treg proliferation, and T-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…ACT using tumor infiltrating lymphocytes (TIL) has shown promise for patients with metastatic melanoma, cervical cancer and ovarian cancer. 11–15 We have previously demonstrated efficacy of TIL therapy for patients with metastatic melanoma. 16 The goal of this study was to assess the feasibility of isolation and expansion, and assessment of in vitro efficacy of the tumor infiltrating lymphocytes from bladder tumor specimens obtained from chemotherapy-naive and exposed cases for future use in adoptive cell therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach that has been used recently is to perform adoptive T-cell therapy (ACT), in which tumor-infiltrating lymphocytes (TIL) are isolated from metastases in patients, massively expanded in vitro, and transferred back into patients. Clinical trials have revealed great efficacy of ACT with an objective response rate of about 40% to 50% and a complete response rate of about 10% to 20% (18)(19)(20)(21)(22). However, the process for generating a large number of TILs can be complex and time consuming; as a result, a high percentage of patients have to drop out during TIL preparation.…”
Section: Introductionmentioning
confidence: 99%